Analysis of Simulation Possibilities by CMOS Integrated Circuits on Switch Level Description - Beniseviciute, R. (Elektronika ir Elektrotechnika, 1999)
Two electronics circuit groups exist (ECL and CMOS), where transistors can be described by control switches. It is the description on a higher level. There is the possibility to apply the programs Verilog and Verifault, when circuits on switch level are simulated. In this case input test vectors are generated automatically. Mixed circuits on logical and switch levels can be simulated. There is principal shortcoming, when precision of simulation is defined by the model level of control switches. The most accurate version of switches is attained, when the transistor is described as resistivity and capacity (RC) switch. The methodics of RC parameter selection for description on Switch-RC level is presented in this article. Simulation of selected groups circuits are realized employing programs Spectre (on transistor level) and Verilog (on Switch-RC level). The results of simulation are compared, average error of 4.58 % was detected. Influence of Switch-RC parameters on circuits groups dynamical characteristics are investigated.